Blood DHA, Choline, and Lutein Concentrations and Their Correlation with Cognitive and Behavioral Outcomes in 18-Month Old Toddlers: Preliminary Findings. (29th May 2020) - Rossen, Larissa; Montgomery, Sarah; Zibrik, Deborah; Dyer, Roger; Oberlander, Tim; Lamers, Yvonne
Abstract: Objectives: The objective of this study was to investigate associations between key nutrients identified as critical for central nervous system development and function, but which are limited in the diet of toddlers, and neurodevelopmental outcomes in toddler-aged children. We hypothesize that higher concentrations of key nutrients are associated with higher neurocognitive development scores. Methods: Cross-sectional baseline data were drawn from 18-month old toddlers residing in Vancouver, Canada, who participated in a partially randomized controlled trial investigating associations between feeding patterns, nutrient biomarker status, and neurodevelopmental outcomes. Cognitive and behavioural outcomes considered for this analysis included: The Bayley Scale of Infant Development (3 rd Ed; BSID-III); Child Behavior Checklist (CBCL); Early Childhood Behavior Questionnaire Very Short Form (ECBQ); and the MacArthur-Bates Communicative Development Inventories (Words & Gestures and Words & Sentences; MCDI-WG & WS). Blood biomarkers of nutrients of interest included plasma concentration of ferritin, lutein, choline, vitamins A and D, and betaine, as well as docosahexaenoic acid (DHA) measured as a percentage of total fatty acids in red blood cells. Results: Sixty-nine toddlers (34 boys, 35 girls) with preliminary data available had a mean gestational age at birth and birthweight of 39.5 weeks and 3.48 kg, respectively. Preliminary (unadjusted) findings show higher levels of DHA corresponded with lower scores of effortful control on the ECBQ (rho = –.35, P  < .01) while higher levels of lutein were associated with higher scores on the MCDI-WG (rho = .33, P  < .05). Conclusions: These preliminary findings may reflect an important association between nutritional status and optimal brain function at 18-months of age, a period of life which is particularly sensitive to nutrient inadequacies. These findings require confirmation in a larger sample size and causality testing of the relationship in a dose-dependency trial. Funding Sources: This study is supported by The University of British Columbia, and the British Columbia Children's Hospital Research Institute, Canada, and is funded by Société des Produits Nestlé S.A.